Reflections on liver transplantation: emerging research and clinical perspectives in 2025 - Alfred Wei-Chieh Kow (Frontiers in Transplantation, 2026)
The 30th Annual Congress of the International Liver Transplantation Society (ILTS), held in Singapore from 28 to 31 May 2025 under the theme “Advancing Liver Transplantation: Embracing Innovation for the Future,” was a landmark meeting—the first ILTS Congress in Southeast Asia and the largest in the Society's history, convening more than 1,200 delegates and 262 invited speakers from 40 countries across 92 scientific sessions and 7 pre-congress workshops. The congress was led by the National University Centre for Organ Transplantation (NUCOT) at the National University Hospital (NUH), with the author serving as Local Chair. This article provides a reflection on the emerging research and clinical perspectives as presented and discussed at the ILTS Annual Congress 2025 in Singapore. We also share the overall organization and experience of the meeting. This is a structured overview of the congress includes its programme architecture, main scientific findings across all subspecialty domains and the legacy Tree of Life project. There is also an in-depth thematic review of the most impactful scientific contributions, with particular attention to robotic and minimally invasive surgery, machine perfusion and donation after circulatory death (DCD) liver transplantation, transplant oncology, artificial intelligence (AI) and precision medicine, and basic and translational science. Collectively, these themes reflect a field at a genuine inflection point, where multiple technological revolutions are converging at clinical maturity whilst enduring challenges of organ scarcity, global equity, and cost sustainability demand continued attention.